Can peritoneal dialysis be continued, as opposed to switching to HD, in end-stage renal disease patients with acute coronary syndrome with pulmonary edema? - Yahn-Bor Chern; Yu-Ling Lin; Hsi-Hao Wang; Shih-Yuan Hung; Min-Yu Chang; Li-Chun Ho; Ching-Fang Wu; Hung-Hsiang Liou; Yi-Che Lee (Renal Failure)
Background Managing acute coronary syndrome (ACS) with pulmonary edema is challenging in end-stage kidney disease (ESKD) patients on dialysis. While hemodialysis (HD) is often chosen for rapid fluid removal, peritoneal dialysis (PD) may better preserve hemodynamic stability in patients prone to circulatory compromise. This study evaluated whether continuing PD in patients who develop ACS and pulmonary edema while already on PD is feasible for improving oxygenation and fluid management without switching to HD.Methods This retrospective single-center study reviewed 13 PD patients who experienced 15 ACS episodes complicated by pulmonary edema. Data collected included demographics, comorbidities, Killip classification, PD regimen modifications, and outcomes. Adjustments to PD prescriptions and their effectiveness were assessed.Results Among the 15 episodes, 11 (73.3%) were successfully managed with PD alone, while 4 (26.7%) required temporary HD due to insufficient fluid removal. Most cases were Killip Class II (20%) or III (73.3%). The average ICU stay was 4 days, and in-hospital mortality was 20%.Conclusions Continuation of PD in patients who develop ACS accompanied by pulmonary edema appears feasible in most cases, provided that PD prescriptions are carefully individualized. Switching to HD is not invariably required, but thoughtful patient selection and close monitoring remain essential to optimize clinical outcomes.